Effective use of MPC for dynamic decoupling of MIMO systems - Dworak P.; Goyal J.K.; Aggarwal S.; Ghosh S. (My University, 2025)
—The article analyses possible ways of using predictive controllers to perform control tasks and dynamic decoupling for dynamic systems with Multiple Inputs and Multiple Outputs (MIMO). The results of experiments on the selected reference plant are presented, showing the effectiveness of individual decoupling methods. These are also compared to those obtained in typical control systems with Proportional-Integral-Derivative (PID) controllers. Recommendations are made on how to tune model predictive controllers (MPC) for their effective use for MIMO plants. © 2019 Kauno Technologijos Universitetas. All rights reserved.